2022
DOI: 10.1002/ejoc.202200087
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and SAR of 2,3‐Dihydro‐1‐benzofuran‐4‐carboxylates: Potent Salicylic Acid‐Based Lead Structures against Plant Stress

Abstract: New 2,3‐dihydro‐1‐benzofuran‐4‐carboxylic acid derivatives have been identified as potent lead structures against drought and cold stress in crops starting from the synthetic exploration of stabilized analogs of the natural product lunularic acid. An optimized Lewis‐acid mediated cyclization gave a short and efficient access to the envisaged 2,3‐dihydro‐1‐benzofuran‐4‐carboxylates. Enantioselective approaches were investigated to assess the potential impact of the chiral center on in vivo activity. Whilst 2,3‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…With emphasis on preserving the beneficial physicochemical properties of a salicylate moiety the carbon C2-bridge of lunularic acid 130 can be included in a 5-membered dihydrofuryl ring preserving the salicylate as is shown in structure 130 (Figure ). Remarkably, 130 and closely related analogues revealed strong in vivo activity, both against drought stress in several broad-acre crops, as well as against cold stress in corn …”
Section: Salicylic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…With emphasis on preserving the beneficial physicochemical properties of a salicylate moiety the carbon C2-bridge of lunularic acid 130 can be included in a 5-membered dihydrofuryl ring preserving the salicylate as is shown in structure 130 (Figure ). Remarkably, 130 and closely related analogues revealed strong in vivo activity, both against drought stress in several broad-acre crops, as well as against cold stress in corn …”
Section: Salicylic Acidmentioning
confidence: 99%
“…113 Remarkably, 130 and closely related analogues revealed strong in vivo activity, both against drought stress in several broad-acre crops, as well as against cold stress in corn. 114…”
Section: Journal Of Agricultural Andmentioning
confidence: 99%
“…Tu et al developed a Cu/SPDO-catalyzed [3+2] cycloaddition to construct 2-aryl-2,3-dihydrobenzofuran scaffolds by quinone esters and styrenes . Recently, Feackenpohl et al reported the lewis acid-catalyzed [3+2] cycloaddition of quinones with phenyl acetylenes to synthesize 2,3-dihydro-1-benzo-furan-4-carboxylates . Unfortunately, there is no report about the [3+2] cyclization of quinones with cyanide compounds to form the benzo­[ d ]­oxazoles.…”
Section: Introductionmentioning
confidence: 99%
“…2,3-Dihydrobenzofurans (DHBs) are important skeletons for bioactive compounds and natural products, and various synthetic approaches have been developed. [1][2][3][4] Among them, benzoquinones (BQs) have been widely utilized as substrates in [3 + 2] cycloaddition with olefins (e.g., styrenes, [5][6][7][8] enol ethers, [9][10][11] allyl silane 12) ) to afford versatile DHBs (Chart 1A). BQs are prepared by the oxidation of hydroquinones (HQs), which can be easily modified by Friedel-Crafts type reactions to the corresponding C2-functionalized hydroquinone (such as compounds bearing an electron-withdrawing group (EWG) at the C2 position, 1, Chart 1C).…”
Section: Introductionmentioning
confidence: 99%